Effect of hydrogen addition on the performance and emission parameters of an SI engine fueled with butanol blends at stoichiometric conditions. (10th August 2015) - Raviteja, S.; Kumar, G.N.
Abstract: Hydrogen is considered as the best fuel due to its excellent combustion properties. But its use as a fuel is confined by its low energy density. In the present investigation an attempt has been made to utilize some of the benefits of hydrogen by using it as an additive in a butanol fueled engine. The experimental study has been carried out on a 4 stroke, single cylinder, manifold electronic fuel injected (EFI) engine mapped to run at stoichiometric conditions. Butanol blends were chosen as the base fuel due to their higher energy density compared to ethanol. A small fraction of hydrogen was injected into the air stream. The engine was run at 3000 RPM at full load condition. The performance, emission and combustion parameters are compared for four concentrations of butanol (10%, 20%, 30%, and 100% by volume of fuel) and two concentrations of hydrogen (5%, and 10% by volume of air) with gasoline. The results indicated that the efficiency of the engine improved upon hydrogen enrichment. An average of 60% reduction was observed in HC and CO emissions with 10% enrichment of hydrogen, whereas the NO emissions almost doubled itself. The combustion analysis showed reduced delay periods, shorter combustion durations, higher cylinder pressures, higher temperatures and improved combustion. Highlights: Effect of hydrogen enrichment on butanol blended gasoline engine was studied. Reduced fuel consumption was observed due to better energy conversion. Lower HC and CO emissions due to better combustion and higher temperatures. Cylinder pressure increased, while delay period and combustion duration reduced.